Evaluation of curcumin-mediated photodynamic therapy on the reverse of multidrug resistance in tumor cells. Issue 1 (2nd January 2020) - Li, Ying; Xiao, Pei; Huang, Zipeng; Chen, Xinru; Yan, Xia; Zhai, Junqiu; Ma, Yan
Abstract : The Apoptosis of resistant tumor cells reduced by curcumin-mediated photodynamic therapy. Abstract : Curcumin (CUR) possesses photosensitive anti-tumor activity. However, photoactive CUR mainly targets tumor cells sensitive to chemotherapy, whereas the effect on multi-drug resistant cancer cells has not been fully investigated. The study aimed to investigate the anti-tumor activity of CUR on resistant MCF-7/ADM cells and its underlying mechanism providing insights into CUR-mediated PDT and a reference for reversing multidrug resistance. Cell apoptosis and morphological changes were detected by Annexin V-FITC/PI double staining and immunofluorescence, respectively. The apoptosis mechanism of CUR-mediated PDT was investigated by detecting the levels of reactive oxygen species (ROS), mitochondrial membrane potential, and related proteins. MTT and apoptosis results showed that CUR-mediated PDT significantly enhanced cytotoxicity and induced considerable cell apoptosis. After treatment with CUR-mediated PDT, cells became round in shape and shrunk, F-actin was loosely arranged, and the nucleus decreased in size. In addition, the level of ROS increased over time compared to the control and peaked at 6 h. CUR-mediated PDT induced alterations in the mitochondrial membrane potential, increased the release of mitochondrial cytochrome C (Cyt-c), and downregulated caspase-3/7/9, PARP, and P-gp. In conclusion, CUR-PDT induced apoptosis in resistant MCF-7/ADM cells primarily through endogenous mitochondrial apoptosis pathway. Besides apoptosis activation in resistant cells, the reverse of multidrug resistance was ascribed to the downregulation of P-gp expression to a degree.